HISTOPATHOLOGY OF THE TELENCEPHALON AND DIENCEPHALON OF T1LAPIA NILOTICA EXPOSED TO SUBLETHAL DOSE OF MALATHION S-[1,2-DI-(ETHOXYCARBONYL ETHYL) DIMETHYL PHOSPHOROTHIOLOTHIONATE] - EDNA A AMPARADO (SEAMEO BIOTROP, 1992)
A 35-day exposure of Tilapia nilotica embryos to sublethal doses of 3.0 ppm and 0.3 ppm malathion, S-[l,2-di-(ethoxycarbonyl ethyl) dimethyl phosphorothiolothionate], commercial grade, EC 57, produces cellular and ultrastructure changes in the brain. A number of nuclear centers of the treated animals are markedly larger than those of the control. Aberrant features observed in day-45 embryos are the neoplastic masses and increased vascularization. Ultrastructure defects include the presence of nuclear blebs, cytoplasmic vacuolations and increased lysosomal bodies.